A New Vision of IgA Nephropathy: The Missing Link - Sallustio, Fabio (Int J Mol Sci, 2019)
IgA Nephropathy (IgAN) is a primary glomerulonephritis problem worldwide that develops mainly in the 2nd and 3rd decade of life and reaches end-stage kidney disease after 20 years from the biopsy-proven diagnosis, implying a great socio-economic burden. IgAN may occur in a sporadic or familial form. Studies on familial IgAN have shown that 66% of asymptomatic relatives carry immunological defects such as high IgA serum levels, abnormal spontaneous in vitro production of IgA from peripheral blood mononuclear cells (PBMCs), high serum levels of aberrantly glycosylated IgA1, and an altered PBMC cytokine production profile. Recent findings led us to focus our attention on a new perspective to study the pathogenesis of this disease, and new studies showed the involvement of factors driven by environment, lifestyle or diet that could affect the disease. In this review, we describe the results of studies carried out in IgAN patients derived from genomic and epigenomic studies. Moreover, we discuss the role of the microbiome in the disease. Finally, we suggest a new vision to consider IgA Nephropathy as a disease that is not disconnected from the environment in which we live but influenced, in addition to the genetic background, also by other environmental and behavioral factors that could be useful for developing precision nephrology and personalized therapy.